Who stole Halloween? - Freeman, Martha, 1956- (New York : Holiday House, 2005)
When nine-year-old Alex and his friend Yasmeen investigate the disappearance of cats in their neighborhood, they stumble onto a larger mystery involving a haunted house and a ghostly cat.
710
Accelerated Reader AR
Keywords: Cats -- Fiction; Kidnapping -- Fiction; Ghosts -- Fiction; Haunted houses -- Fiction; Halloween -- Fiction; Mystery and detective stories